IMPLEMENTASI TWO-FACTOR AUTHENTICATION (2FA) DAN FIREWALL POLICIES DALAM MENGAMANKAN WEBSITE - Herdiantoro, Hero Raka; Islami, M Reza Redo (Universitas Muhammadiyah Metro, 2023)
The industrial era 4.0 requires all aspects of people's lives to take advantage of technology to make it easier to solve a problem, one of the very popular technologies is the website, websites are becoming popular because they can be accessed through various platforms, the popularity of websites causes increased attacks on websites. Cyber criminals usually steal accounts from website administrators to manipulate data and information, for this reason, it is necessary to have a security method to protect websites from attacks. Various account security methods have been developed, one of which is the two-factor authentication (2FA) method, this method is used to anticipate if the administrator's account is stolen by a cybercriminal, if someone else gets the account, the perpetrator must get the second password sent. system to the victim's email or cellphone number, so to be able to enter the website, two authentication steps are needed. In addition to 2FA, this research will utilize a firewall to allow multiple addresses (IP addresses) to access administrator pages, so that if the perpetrator is outside the permitted address, the perpetrator still cannot enter the website. By utilizing 2FA and firewall policies, websites will have more protection from cyber security threats.